(untitled) (Journal of Universal Science Research, 2023)
Medical terminology has an extensive and rich history in Latin and Greek languages. When the Romans conquered Greece, the knowledge and language of both cultures merged, resulting in new medical concepts regarding disease treatment and containment. Medical records were chronicled by hand, creating medical terms and books. For an example of a medical etymology, the word ‘diabetes’ is borrowed from the Greek word meaning a siphon.